2018
DOI: 10.1007/s10811-018-1589-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of Anabaena variabilis population by single and mixed steroid hormones

Abstract: Many contaminants which are toxic and adversely affect living organisms enter surface waters. Among them, there are endocrine compounds such as steroid hormones, which can disrupt the endocrine system causing an adverse effect on the physiology of aquatic organisms. In the literature, there is not enough information about the influence of steroid hormones on phytoplankton growth. Therefore, the aim of this research was to study the effect of estrogens (estrone, 17ß-estadiol, 17-α-ethinylestradiol, and estriol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…A similar phenomenon was observed in our study because low concentrations of E1, E3, EE2, and PRO stimulated the growth of M. aeruginosa. Previous studies have shown that hormones inhibited the growth of cyanobacteria Anabaena variabilis (Czarny et al 2019a). Similar to the present study, EE2 and PRO were the most toxic of all the tested hormones and the achieved 14-day EC 50 values were 48.59 and 82.95 mg L −1 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A similar phenomenon was observed in our study because low concentrations of E1, E3, EE2, and PRO stimulated the growth of M. aeruginosa. Previous studies have shown that hormones inhibited the growth of cyanobacteria Anabaena variabilis (Czarny et al 2019a). Similar to the present study, EE2 and PRO were the most toxic of all the tested hormones and the achieved 14-day EC 50 values were 48.59 and 82.95 mg L −1 .…”
Section: Discussionsupporting
confidence: 89%
“…The achieved 14-day EC 50 values for mixed hormones for A. variabilis, C. vulgaris, and S. armatus were 37. 00-89.46, 47.89-75.30, and 70.54-697.26 mg L −1 , respectively (Czarny et al 2019a, b). Comparing the results, it can be estimated that M. aeruginosa were less sensitive than A. variabilis and C. vulgaris, and more sensitive than S. armatus.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…EE2 was reported to inhibit growth of different microalgal strains (Table 8, Table S2). EE2 caused 50% toxicity/inhibition of Pseudokirchneriella subcapitata / Raphidocelis subcapitata growth [103,176], Scenedesmus / Desmodesmus strains [84,103,176,177,178], Chlorella vulgaris growth [178] and Dunaliella salina growth [179], the diatom Navicula incerta ’s growth [180] and the cyanobacteria Microcystis aeruginosa [103] and Anabaena variabilis [181].…”
Section: Inhibitory Effect Of Pharmaceuticals and Personal Care Prmentioning
confidence: 99%
“…This bacterium is found in the aquatic environment and has been known as producing neurotoxin harmful to the ecosystem. [25] Using 1,4-benzoquinone (pBQ) as a redox mediator, and reduced graphene oxide (rGO)-coated indium tin oxide as an anode, we could achieve maximum photocurrent of 223 μA cm À 2 at 0.4 V (vs. Ag/AgCl) and Incident photon to current efficiency (IPCE) of 0.50 % with white light. From a complete cell constructed with a Pt/C air cathode, the maximum power density of 13 μW cm À 2 at a current density of 115 μA cm À 2 was achieved.…”
Section: Introductionmentioning
confidence: 99%